Lysosome Positioning Influences mTORC2 and AKT Signaling - Jia, Rui (Mol Cell, 2019)
Growth factor signaling is initiated at the plasma membrane and propagated through the cytoplasm for eventual relay to intracellular organelles such as lysosomes. The serine/threonine kinase mTOR participates in growth factor signaling as a component of two complexes, mTORC1 and mTORC2. mTORC1 associates with lysosomes and its activity depends on the positioning of lysosomes within the cytoplasm, although there is no consensus regarding the importance of perinuclear vs. peripheral distribution. mTORC2 and its substrate kinase AKT have a widespread distribution, but they are thought to act mainly at the plasma membrane. Using cell lines with knock out of components of the lysosome-positioning machinery, we demonstrate that perinuclear clustering of lysosomes delays reactivation of not only mTORC1 but also mTORC2 and AKT upon serum replenishment. We also show partial association of mTORC2 and AKT with lysosomes. These experiments demonstrate that mTORC1, mTORC2 and AKT constitute a module for growth factor signaling that is sensitive to lysosome positioning.